2022
DOI: 10.1186/s12879-022-07173-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term immune responses in patients with confirmed novel coronavirus disease-2019: a 9-month prospective cohort study in Shanghai, China

Abstract: Background The duration of antibodies against SARS-CoV-2 in Covid-19 patients remains uncertain. Longitudinal serological studies are needed to prevent disease and transmission of the virus. Methods In 2020, 414 blood samples were tested, obtained from 157 confirmed Covid-19 patients, in a prospective cohort study in Shanghai. Results The seropositive rate of IgM peaked at 40.5% (17/42) within 1 month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Some studies performed at the beginning of the COVID-19 pandemic showed that the amount of anti-SARS-COV-2 IgM/IgG antibodies decreased in several months post onset of symptoms [ 4 , 5 ] . However, Gong X et al found that anti-SARS-CoV-2 IgG can last for at least 9 months in patients with a history of natural infection [ 6 ] . Kaygusuz S et al also showed that both IgG and neutralization antibodies levels continued unabated after 9 months of follow-up [ 7 ] .…”
mentioning
confidence: 99%
“…Some studies performed at the beginning of the COVID-19 pandemic showed that the amount of anti-SARS-COV-2 IgM/IgG antibodies decreased in several months post onset of symptoms [ 4 , 5 ] . However, Gong X et al found that anti-SARS-CoV-2 IgG can last for at least 9 months in patients with a history of natural infection [ 6 ] . Kaygusuz S et al also showed that both IgG and neutralization antibodies levels continued unabated after 9 months of follow-up [ 7 ] .…”
mentioning
confidence: 99%